Time advice and learning questions in computer simulations - Rey, Günter Daniel (Australasian Journal of Educational Technology, 2011)
Students (N = 101) used an introductory text and a computer simulation to learn fundamental concepts about statistical analyses (e.g., analysis of variance, regression analysis and General Linear Model). Each learner was randomly assigned to one cell of a 2 (with or without time advice) x 3 (with learning questions and corrective feedback, with learning questions without feedback or without learning questions) between subjects factorial design. Time spent with the simulation as well as retention and transfer tests were used as dependent measures. Neither the time advice presented immediately before students chose to finish the simulation nor the learning questions presented during the simulation significantly improves learners' retention or transfer performances. Students who were asked to employ more time on the computer simulation or who received learning questions with corrective feedback spent significantly more time with the simulation than did students for whom the time advice or the learning questions were absent. The results were discussed on the basis of the cognitive theory of multimedia learning and the cognitive-affective theory of learning with media, as well as in conjunction with adaptive computer simulations.